2015
DOI: 10.1021/ml500458t
|View full text |Cite
|
Sign up to set email alerts
|

An Orally Available BACE1 Inhibitor That Affords Robust CNS Aβ Reduction without Cardiovascular Liabilities

Abstract: BACE1 inhibition to prevent Aβ peptide formation is considered to be a potential route to a diseasemodifying treatment for Alzheimer's disease. Previous efforts in our laboratory using a combined structure-and propertybased approach have resulted in the identification of aminooxazoline xanthenes as potent BACE1 inhibitors. Herein, we report further optimization leading to the discovery of inhibitor 15 as an orally available and highly efficacious BACE1 inhibitor that robustly reduces CSF and brain Aβ levels in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Other classes of amino azines inhibitors are compounds containing the amino‐oxazoline and xanthene cores, which showed a remarkable inhibition potency against BACE1. However, these compounds were found to exhibit high P‐gp efflux ratio . Functionalization of the xanthene core led to compound 20 possessing a 3‐aza‐2‐fluoroxanthene moiety reported by Cheng et al Inhibitor 20 is a highly effective BACE1 inhibitor that significantly reduced the brain and CSF Aβ levels in both rats and nonhuman species .…”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 99%
See 3 more Smart Citations
“…Other classes of amino azines inhibitors are compounds containing the amino‐oxazoline and xanthene cores, which showed a remarkable inhibition potency against BACE1. However, these compounds were found to exhibit high P‐gp efflux ratio . Functionalization of the xanthene core led to compound 20 possessing a 3‐aza‐2‐fluoroxanthene moiety reported by Cheng et al Inhibitor 20 is a highly effective BACE1 inhibitor that significantly reduced the brain and CSF Aβ levels in both rats and nonhuman species .…”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 99%
“…Other hydrogen bonds formed between the oxygen of the dihydropyran and Tyr198. The pyridyl nitrogen formed an extra hydrogen bond with Ser229 (Figure ) …”
Section: Bace1 As a Potential Target For The Treatment Of Alzheimer'smentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence alignment analysis showed that the amino acid sequences of human BACE1 and BACE2 gene coding regions are 45% identical and 75% homologous [22]. Numerus crystal structures of BACE1 have been resolved with and without inhibitor in its active site [23][24][25][26][27][28][29][30][31][32]. BACE1 contains an N-terminal protease domain, a connecting strand, a transmembrane region, and a cytosolic domain [23].…”
Section: Function and Structure Of β-Secretasementioning
confidence: 99%